PENGARUH MOTIVASI BELAJAR DAN STRES SEKOLAH TERHADAP PERILAKU TRUANTISME SISWA SMKN 1 GERIH - yuni Harmawati; Oviany Septiana (Journal of Civics and Moral Studies, 2025)
Truancy, or truancy, is a serious problem in education because it significantly impacts students' academic achievement and character development. This study aims to analyze the extent to which learning motivation and school stress contribute to the emergence of truancy in vocational high school students. This study used a quantitative correlational method involving 60 students of SMKN 1 GERIH, selected through accidental sampling with a 10% margin of error. The data collection instrument was a structured questionnaire with a Likert scale that had previously undergone validity and reliability testing. Data analysis used multiple linear regression using SPSS version 25. The results showed that learning motivation had a significant negative effect on truancy, while school stress had a significant positive effect. Simultaneous testing proved that both predictors contributed 61.5% to the variance in truancy. The implications of this study emphasize the urgency of developing counseling-based intervention programs to optimize academic motivation and stress management in vocational schools.